For the first one you need to first figure out how far the first guy has traveled when the second cyclist starts biking. That is 3 hours times 6 miles per hour = 18miles. Now you set up the two equations for the bicyclist.
1. y=6x+30 : y=miles, x=hours
2. y=10x : " "
There are many methods to solve from here I will perform substitution.
So E is your answer 7.5 hours.
I have to clock into work now so I'll have to leave the second question to someone else. Hope this helps and don't forget to thank !